Coxiella burnetii Infections in Small Ruminants and Humans in Switzerland. Issue 1 (29th April 2015) - Magouras, I.; Hunninghaus, J.; Scherrer, S.; Wittenbrink, M. M.; Hamburger, A.; Stärk, K. D. C.; Schüpbach‐Regula, G.
Summary: The recent Q fever epidemic in the Netherlands raised concerns about the potential risk of outbreaks in other European countries. In Switzerland, the prevalence of Q fever in animals and humans has not been studied in recent years. In this study, we describe the current situation with respect to Coxiella (C.) burnetii infections in small ruminants and humans in Switzerland, as a basis for future epidemiological investigations and public health risk assessments. Specific objectives of this cross‐sectional study were to (i) estimate the seroprevalence of C. burnetii in sheep and goats, (ii) quantify the amount of bacteria shed during abortion and (iii) analyse temporal trends in human C. burnetii infections. The seroprevalence of C. burnetii in small ruminants was determined by commercial ELISA from a representative sample of 100 sheep flocks and 72 goat herds. Herd‐level seroprevalence was 5.0% (95% CI: 1.6–11.3) for sheep and 11.1% (95% CI: 4.9–20.7) for goats. Animal‐level seroprevalence was 1.8% (95% CI: 0.8–3.4) for sheep and 3.4% (95% CI: 1.7–6) for goats. The quantification of C. burnetii in 97 ovine and caprine abortion samples by real‐time PCR indicated shedding of >10 4 bacteria/g in 13.4% of all samples tested. To our knowledge, this is the first study reporting C. burnetii quantities in a large number of small ruminant abortion samples. Annual human Q fever serology data were provided by five major Swiss laboratories. Overall, seroprevalence in humans ranged between 1.7% and 3.5% from 2007 to 2011, and no temporal trends were observed. Interestingly, the two laboratories with significantly higher seroprevalences are located in the regions with the largest goat populations as well as, for one laboratory, with the highest livestock density in Switzerland. However, a direct link between animal and human infection data could not be established in this study.